(untitled) (Research, Society and Development, 2021)
Introduction: Obesity is a chronic, multifactorial disease that generates systemic repercussions; characterized by a Body Mass Index (BMI) greater than 30. Social isolation in the COVID-19 pandemic directly interfered in the treatment of obese patients and sickened patients before without comorbidity. Methodology: This is a qualitative literature review, with a search for studies in the Virtual Health Library (VHL), Google Scholar, PubMed and Scientific Library Online (SciELO) databases. For the research, the descriptors COVID-19, social isolation, obesity, mental health and eating disorders were used. Publications between 2017 and 2021 in Portuguese and English available in full text were included. 15 articles were selected from the 71 found. Results and discussion: it was noticed that isolation interferes negatively in the treatment of obese patients, as places for physical exercise were restricted and home confinement makes treatment difficult. Another problem is the development of binge eating, as food is being used to relieve anxiety, depression and stress problems. Conclusion: COVID-19 caused problems that go beyond cases of virus infection, as social isolation directly affected the treatment of obese patients.